Thymus gland and thymic dysfunctions in children - Tamara Turcanu; Elena Dolapciu (Romanian Journal of Pediatrics)
The thymus is the organ that has gained significant awareness in the last two centuries, being considered the main donor of cells for the lymphatic system, much like the bone marrow is the donor of cells for the cardiovascular system. Currently, knowledge regarding the thymus gland has considerably improved. Thymic dysfunctions encompass congenital and acquired conditions, which manifest through organ hypoplasia or hyperplasia, as well as formations/tumors of the anterior mediastinum.